1998
DOI: 10.1001/jama.279.21.1709
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship Between Cancer Patients' Predictions of Prognosis and Their Treatment Preferences

Abstract: Context.-Previous studies have documented that cancer patients tend to overestimate the probability of long-term survival. If patient preferences about the trade-offs between the risks and benefits associated with alternative treatment strategies are based on inaccurate perceptions of prognosis, then treatment choices may not reflect each patient's true values.Objective.-To test the hypothesis that among terminally ill cancer patients an accurate understanding of prognosis is associated with a preference for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
834
2
14

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,209 publications
(881 citation statements)
references
References 33 publications
(22 reference statements)
31
834
2
14
Order By: Relevance
“…With substantial uncertainty in prognosis and patient preferences for life support, more frequent provision of prolonged mechanical ventilation would be expected. (12,28,31,32) However, this default strategy was associated with unanticipated high mortality, profound and chronic disability, as well as significant financial stress and caregiving demands for families-the same poor outcomes that most adults with serious illness report that they would choose to avoid were they to understand the risk. (33) What can be done to help decision makers set reasonable goals for patient care as well as to plan for the unique needs of patients who subsequently transition from acute to chronic critical illness?…”
Section: Discussionmentioning
confidence: 99%
“…With substantial uncertainty in prognosis and patient preferences for life support, more frequent provision of prolonged mechanical ventilation would be expected. (12,28,31,32) However, this default strategy was associated with unanticipated high mortality, profound and chronic disability, as well as significant financial stress and caregiving demands for families-the same poor outcomes that most adults with serious illness report that they would choose to avoid were they to understand the risk. (33) What can be done to help decision makers set reasonable goals for patient care as well as to plan for the unique needs of patients who subsequently transition from acute to chronic critical illness?…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with advanced disease overestimate their prognosis, and more than half are clearly overoptimistic. For example, Weeks et al, (1998) found in a large study of inpatients with advanced cancer that 58% were overly optimistic about their prognosis compared to their physician . These patients were much more likely to request aggressive medical interventions, although their survival was not improved when compared to those who did not pursue aggressive care.…”
Section: Discussionmentioning
confidence: 99%
“…El cómo la notica es discutida o conversada con el paciente puede afectar la comprensión de la información 3,[12][13][14][15] , del pronóstico de la enfermedad [14][15] , la satisfacción con la atención médica [15][16] , el nivel de esperanza frente a la enfermedad 17 , y el posterior ajuste o adaptación psicológica [18][19][20][21][22][23] .…”
Section: Consecuencias De Una Mala Noticiaunclassified